Has the Propensity to Pay Out Declined? - Grullon, Gustavo; Paye, Bradley; Underwood, Shane; Weston, James P. (Journal of Financial and Quantitative Analysis, 2011)
Abstract Recent studies document both a significant decline in firms’ propensity to pay dividends and a significant increase in firms’ propensity to repurchase shares and issue equity over the past 30 years. In this paper we test whether firms’ net cash disbursements to equity holders have declined in a pattern similar to firms’ propensity to pay dividends. Contrary to the evidence using dividends, we find no evidence that the conditional propensity to distribute net cash to equity holders has declined over the past 3 decades. Surprisingly, we find that, conditional on firm characteristics, net payout yields have been increasing over time.